Cross-linked polyelectrolyte for direct methanol fuel cells applications based on a novel sulfonated cross-linker - Li, Mingyu; Zhang, Gang; Xu, Shuai; Zhao, Chengji; Han, Miaomiao; Zhang, Liyuan; Jiang, Hao; Liu, Zhongguo; Na, Hui (Journal of power sources, 2014)
A novel type of cross-linked proton exchange membrane of lower methanol permeation and high proton conductivity is prepared, based on a newly synthesized sulfonated cross-linker: carboxyl terminated benzimidazole trimer bearing sulfonic acid groups (s-BI). Compared to membranes cross-linked with non-sulfonated cross-linker (BI), SPEEK/s-BI-n membranes show higher IEC values and proton conductivities. Meanwhile, oxidative stability and mechanical property of SPEEK/s-BI-n membranes are obviously improved. Among SPEEK/s-BI-n membranes, SPEEK/s-BI-2 exhibits high proton conductivity, low swelling ratio (0.122 S cm−1 and 15.2% at 60 °C, respectively) and low methanol permeability coefficient. These results imply that the cross-linked membranes prepared with the newly sulfonated cross-linker are promising for the direct methanol fuel cells (DMFCs) application. •Cross-linker with proton conductive group was designed and synthesized.•A comparison between the sulfonated and non-sulfonated cross-linkers was made.•By using the sulfonated cross-linker, SPEEK has been successfully modified.•The result membranes showed low methanol crossover as well as high conductivity.•The oxidative stability of the result membranes was much improved also.